If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19x + -5 = 7 + 13x Reorder the terms: -5 + 19x = 7 + 13x Solving -5 + 19x = 7 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -5 + 19x + -13x = 7 + 13x + -13x Combine like terms: 19x + -13x = 6x -5 + 6x = 7 + 13x + -13x Combine like terms: 13x + -13x = 0 -5 + 6x = 7 + 0 -5 + 6x = 7 Add '5' to each side of the equation. -5 + 5 + 6x = 7 + 5 Combine like terms: -5 + 5 = 0 0 + 6x = 7 + 5 6x = 7 + 5 Combine like terms: 7 + 5 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 6.1x-3=5.1x | | (6cd^2+4cd)-(3cd^2-9cd^2-9cd+5)= | | 6+6q=9+5q | | c^2+6cg-27g^2=0 | | 7+(-5+4q)+(-7q-4)= | | (4x-3)(x-5)=0 | | 12x+4=6x+14 | | 3[x-2(x-5)]-1=-3x+29 | | y^2-3y-28=0 | | 6(w-5)=8w+44 | | (5x^2+2)(2x-5)= | | 3+58=8 | | x^2+8-33=0 | | 245=99.8t-5t^2 | | 3x+3-34=5 | | 4K+20=108 | | 3s^2-7s=0 | | 3x+11=9x | | 10x=4x-9 | | -4=-2j-2 | | 2+9x=29 | | -7x-2=44+8x | | 42=2y+2 | | x^2+7x-18x+9= | | (10r+9)-(12r-5)= | | 144v^2-100=0 | | 5y+20=6y-3 | | X-3x=c | | 7(n-12)= | | 72=-6k | | -63=-3x | | 4c^2+12c+9= |